2019
DOI: 10.1021/acs.jchemed.8b00965
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Understanding in Biochemistry Using 3D Printing and Cheminformatics Technologies: A Student Perspective

Abstract: Students often approach biochemistry with a degree of trepidation with many considering it one of the more difficult subjects. This is, in part, due to the necessity of making visual images of submicroscopic concepts. Molecular interactions underpin most biological processes; therefore, mastering these concepts is essential. Understanding the forces and mechanisms that underpin protein–ligand interactions is a key learning goal for mastering the protein structure–function relationship. We intended to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
13
0
3
Order By: Relevance
“…This is due in part to the growing demand of cheminformaticians, bioinformaticians, and biological data sciences in the job market (Attwood et al, 2017). Another reason is that the integra-tion of the use of cheminformatics software has been reported to improve students' visual and spatial abilities (Lohning et al, 2019). It has also been reported that the perception of secondary school students towards the integration of bioinformatics in the curriculum is also very positive in improving their learning (Machluf et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This is due in part to the growing demand of cheminformaticians, bioinformaticians, and biological data sciences in the job market (Attwood et al, 2017). Another reason is that the integra-tion of the use of cheminformatics software has been reported to improve students' visual and spatial abilities (Lohning et al, 2019). It has also been reported that the perception of secondary school students towards the integration of bioinformatics in the curriculum is also very positive in improving their learning (Machluf et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Algunas investigaciones han recomendado utilizar una metodología multifacética, incorporando numerosos enfoques que incluyen el aprendizaje cooperativo, enfoques con casos clínicos, mapas conceptuales, modeladores virtuales, multimedia, webinars, entre otras, las cuales han mostrado resultados positivos en aspectos como: el rendimiento académico de los estudiantes, la motivación por el aprendizaje de conceptos bioquímicos y la reducción en los errores conceptuales (Cookmeyer, et. Al., 2017;Lohning, Hall, & Dukie, 2019). Además, el aprendizaje en contexto tiene la posibilidad de ser utilizado con enfoques combinados mediante el uso de herramientas propias de la bioinformática, asistida por el internet y en general con el uso de las Tecnologías de la Información y la Comunicación (TIC) (Macaulay, Van Damme, & Walker, 2009 ;Vaughan, 2007).…”
Section: Antecedentesunclassified
“…El dibujo y la distribución de carga en la fracción de proteína propuesta por el estudiante 10 son similares a las propuestas por otros estudiantes, por lo que se evidencia el progreso en la de los conceptos aminoácidos, enlace peptídico, proteínas, estructura primaria, estructura secundaria, distribución de cargas y punto isoeléctrico, gracias a las actividades virtuales en contexto y al uso de herramientas bioinformáticas, resultado que complementa los reportados por otros investigadores (Lohning, Hall, & Dukie, 2019;Macaulay, Van Damme, & Walker, 2009).…”
Section: Membrana Bilipídicaunclassified
See 1 more Smart Citation
“…3D printing has become prevalent within chemical education, with numerous examples in the recent literature. , 3D printing has been used in chemical education toward improving student understanding in lecture through providing hands-on interactive projects, enhancing laboratory methods through hands-on learning and the development of libraries of 3D models for use across the curriculum. , The usefulness, simplicity, and flexibility of 3D printing, even in its infancy as a technology, cannot be overstated with respect to chemical education. It is with this perspective that the problem of board-based instruction in distance-learning was approached.…”
Section: Introductionmentioning
confidence: 99%